1993
DOI: 10.1177/089443939301100404
|View full text |Cite
|
Sign up to set email alerts
|

Economics: Microcomputers in the College Classroom—A Review of the Academic Literature

Abstract: During the past I5 years, numerous articles have appeared in academic literature concerning the use of microcomputers in the college economics curriculum. This paper presents a brief review of this literature. The authors discover that the specific topics and issues addressed in this literature are diverse. However, five major content themes are revealed: (I) implementation of programs and/or course procedures, (2) presentation of new computer programs, (3) critical software reviews, (4) overviews of the state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The issue of implementing new technology in economics is not new. Grimes and Ray (1993) summarize the use of computers in college economics courses over the past 25 years, focusing on the use of tutorials and simulations to reinforce economic concepts and principles. More recently, Cardell et al (1996) describe their experience integrating computers, economic data, and in-class economic experiments with traditional lectures in economics courses.…”
Section: Resultsmentioning
confidence: 99%
“…The issue of implementing new technology in economics is not new. Grimes and Ray (1993) summarize the use of computers in college economics courses over the past 25 years, focusing on the use of tutorials and simulations to reinforce economic concepts and principles. More recently, Cardell et al (1996) describe their experience integrating computers, economic data, and in-class economic experiments with traditional lectures in economics courses.…”
Section: Resultsmentioning
confidence: 99%
“…Attendance in her technology classes was as high or higher than in a traditional class. In an article reviewing the literature on using computers in economics classes, Grimes and Ray (1993) conclude that computerized tutorials and simulations were shown to enhance student learning and perhaps to improve attitudes toward economics.…”
Section: Using Technology In Teaching: Viewpoints and Researchmentioning
confidence: 99%
“…A review of this literature by Grimes and Ray [6] indicates that CAI is often found to increase student learning. The evidence to date suggests that computerized simulations may be more effective than computerized tutorials and that CAI in general is most effective for students at either end of the grade distribution.…”
Section: Student Study Choices In the Principles Of Economics: A Casementioning
confidence: 99%
“…Students who had not previously studied economics may have chosen CAI in order to "catch up" with their classmates who had taken a prior course in high school or college. 6 Again, the negative ACT coefficient may indicate that students with lower levels of overall academic aptitude seek out additional study aids, such as CAI, to remediate their academic position.…”
mentioning
confidence: 99%